Determinants of Vote Buying in Local Head Election in Indonesia - Putra, Heru Syah (Jurnal Bina Praja, 2017)
The local head election in Indonesia suffers from vote buying. However, there is a lack of study compared to vote buying case in Indonesia, especially quantitative study. Therefore, this study aims to fill the gap. The purpose is to estimate the effect of individual and community characteristics on the probability of voter to consider money or gifts in a local head election. This study uses the data from Indonesia Family Life Survey 5 (IFLS5) conducted in 2014/2015 for 29,788 respondents. As the response is a binary data, the Linear Probability Model (LPM) and logit model is utilized. The result shows that both individual and community characteristics affect vote buying in Indonesia. Voters with tertiary education are far less likely to consider money or gift by 29.1% than others. By using logit test, the coefficient is corrected. Voters with a university degree tend to not engage in vote buying by 0.27 times than the others. This study finds other interesting findings that gender matter in vote buying in Indonesia. Female voters tend to consider money or gift more than male by 2.44%. Voters who live in rural areas have a higher probability to consider vote buying by 4.55%. Living in the internet-connected community may reduce the probability of vote buying. The coefficient indicates that those with internet access have less probability to consider money or gift in an election by 1.35%. Living in a community with high social awareness makes voters less vulnerable to vote buying. The coefficient indicates that they have less possibility to consider money by 2.44% than those living in communities with less social awareness. Thus, the strategy to eliminate vote buying should be adjusted to the character of voters in a certain community.